Use of the Electrodiagnostic Entrustable Professional Activity for Competency Assessment in Physical Medicine and Rehabilitation Training Programs. (January 2020) - Baer, Heather R.; Gilbert, Aaron R.; Forster, Jeri E.; Ketchum, Nicholas C.; Mallow, Michael; Nguyen, Vu Q. C.
Abstract : Abstract: Entrustable professional activities have emerged as a means for the evaluation of resident competency that is expressed in terms of the assessed need for supervision. Recently, 19 physical medicine and rehabilitation–specific entrustable professional activities were published ( Am J Phys Med Rehabil . 2017;96:762–764). The electrodiagnostic entrustable professional activity and six new electrodiagnostic entrustable professional activities subcategories (observable practice activities) were piloted as an entrustable professional activities/observable practice activities set within five residency programs. Survey-based (quantitative) and open-ended (qualitative) feedback was collected from participants. Participating attendings found this method feasible and generally reported satisfaction with the entrustable professional activities/observable practice activities as a means of providing feedback to residents. Residents were less clear on the added value of this approach. Qualitative data supported the need for adjustments to the entrustment scale to allow for more gradations within supervisory levels, a standardized orientation of residents to the use of observable practice activities and an increased quantity of assessments for each observable practice activities category to allow for demonstration of resident progress toward independence. Use of the electrodiagnostic entrustable professional activity/observable practice activities set shows promise as a means for observational competency assessment in the outpatient setting. However, feedback acquired through this pilot study suggests changes that could be made to improve future implementation. Abstract : Supplemental digital content is available in the text.